Food consumption patterns in different regions of the Kingdom of Saudi Arabia: Household cross- sectional study - Randah M. Alqurashi; Samar M. Abdalla; Albandari Bin Ammar; Israa M. Shatwan; Abdulrahman A. Alsayegh; Aseel N. Alnasser; Jewaher T. Alfadhliah; Ghadir A. Fallata; Omar A. Alhumaidan; Nahla M. Bawazeer (Applied Food Research)
This study investigated food consumption patterns in the Kingdom of Saudi Arabia by categorizing them into ten primary food groups. Data from five selected regions (Riyadh, Jazan, Jeddah, Hail, and Al-Ahsa) were analyzed to determine regional dietary variations. A cross-sectional household research design was employed, utilizing a 3-day food records method. Participants responsible for home cooking were asked to record their food data. Data were analyzed using descriptive statistics. The results indicate significant regional variations in food consumption patterns. For instance, in Hail region there was higher consumption of cereals, particularly rice used in the local dish ''Kabsa,'' and legumes such as fava beans and chickpeas. Jazan had a high intake of starchy roots such as potatoes. Meat, fish, and eggs were regularly consumed in Jazan and Jeddah, whereas milk and dairy products were more prevalent in Riyadh and Jeddah. Vegetables and fruits were commonly consumed in both Hail and Riyadh. This study highlights the growing trend in food consumption outside the home, reflecting changing lifestyles in the Kingdom of Saudi Arabia. The analysis of variance (ANOVA) showed significant variability in daily food consumption among different food groups, and there was a strong correlation between the amount of daily food consumed across different regions. These findings provide valuable insights for policymakers and health professionals to formulate balanced and nutritious dietary recommendations, with the ultimate goal of improving public health outcomes in Saudi Arabia through region-specific nutritional policies and interventions. Further research and policy development are necessary to adapt strategies effectively to the unique dietary habits and challenges of each region.